ANALYSIS OF THE EFFECT OF KNOWLEDGE AND UNDERSTANDING OF TAX REGULATIONS, TAX RATE, TAX SANCTIONS, SERVICE QUALITY, AND SELF ASSESSMENT ON TAXPAYER COMPLIANCE WITH TAX AMNESTY PROGRAM IN PRATAMA MEDAN TAX OFFICE - Ramaly, Hartono (Asosiasi Dosen Akuntansi Indonesia, 2021)
Tax in general means citizens’ obligation to actively participate in the national development according to laws. However, their low obedience has caused tax revenue does not achieve the target, and it makes the researcher interested in analyzing the influence of Knowledge and Understanding about Taxation, Tax Rate, Tax Sanction, Service Quality, and Self-Assessment on Taxpayers’ Compliance at KPP Pratama, Medan Kota. The objective of the research was to find out the empirical evidence of the Influence of Knowledge and Understanding about Taxation on Taxpayers’ Compliance, the influence of Tax Rate on Taxpayers’ Compliance, the influence of Tax Sanction on Taxpayers’ Compliance, Service Quality on Taxpayers’ Compliance, and Self-Assessment on Taxpayers’ Compliance at KPP Pratama, Medan Kota. The population was 11,456 taxpayers who had participated in Tax Amnesty Program at KPP Pratama, Medan Kota. The data were analyzed by using logistic regression analysis. The result of the research showed that simultaneously there was significant influence at 65% of Knowledge and Understanding about Taxation, Tax Rate, Tax Sanction, Service Quality, and Self-Assessment on Taxpayers’ Compliance. Partially, Knowledge and Understanding about Taxation did not have any significant influence on Taxpayers’ Compliance, Tax Rate had negative but significant influence on Taxpayers’ Compliance, Tax Sanction, Service Quality, and Self-Assessment had positive ad significant influence on Taxpayers’ Compliance.